2016
DOI: 10.1177/2277975216644807
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Revenue Diversification and Efficiency of Banks in India

Abstract: This article attempts to understand how income diversification influences efficiency of scheduled commercial banks in India across ownership and over crises periods. We explore two competing hypotheses prevalent in the literature—strategic focus and conglomeration. Input-oriented technical and pure technical efficiency scores are calculated using data envelopment analysis following two approaches in the literature—intermediation and operating. We find support for the conglomeration hypothesis under the interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Berger et al (2010) assert that diversification is associated with the lower profit and higher cost of the Chinese banking industry. Similarly, the revenue diversification has a mixed performance on the efficiency of banks (Sarkar, 2016) and adversely influences the efficiency (Phan et al, 2018). But, there is scarce in the research on the impact of the bank diversification on bank's productivity in India.…”
Section: 23mentioning
confidence: 99%
“…Berger et al (2010) assert that diversification is associated with the lower profit and higher cost of the Chinese banking industry. Similarly, the revenue diversification has a mixed performance on the efficiency of banks (Sarkar, 2016) and adversely influences the efficiency (Phan et al, 2018). But, there is scarce in the research on the impact of the bank diversification on bank's productivity in India.…”
Section: 23mentioning
confidence: 99%
“…The relationship between income diversification and bank performance has been empirically analyzed primarily for developed economies such as USA and European Unions (Acharya et al, 2006;Brighi and Venturelli, 2014;Chen and Kao, 2014;Chen and Lai, 2017;Chronopoulos et al, 2011;Deng and Elyasiani, 2008;DeYoung and Roland, 2001;Edirisuriya et al, 2015;Elsas et al, 2010;Elyasiani and Wang, 2012;Goddard et al, 2008;Huang and Chen, 2006;Jouida et al, 2017;Klein and Saidenberg, 2010;Köhler, 2014;Laeven and Levine, 2007;Lepetit et al, 2008;Mercieca et al, 2007;Rime and Stiroh, 2003;Schmid and Walter, 2009;Stiroh, 2004;Stiroh and Rumble, 2006) and developing economies such as Brazil (Tabak et al, 2011), China (Berger et al, 2010;Li and Zhang, 2013;Liang et al, 2018;Meng et al, 2018;Nguyen and Nghiem, 2016;Zhou, 2014), India (Nguyen and Nghiem, 2016; Bank performance in India Pennathur et al, 2012;Sarkar, 2016;Sharma and Anand, 2018;Trivedi, 2015), Malaysia (Brahmana et al, 2018;Nguyen, 2018), Philippines (Meslier et al, 2014;Nguyen, 2018) and Vietnam (Nguyen, 2018;…”
Section: Empirical Literaturementioning
confidence: 99%
“…Trivedi (2015) revealed that there had been a positive impact of non-interest income and fee-based income on the total operating income and bank profitability for the period 2005-2012. Similarly, Sarkar (2016) investigated the relationship between income diversification and technical and pure technical efficiency for Indian banks sample during 1999-2000 to 2012-2013. They confirmed that revenue diversification has positive and significant impact on both efficiency estimates under intermediation approach thus supporting the conglomeration hypothesis.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Most of the empirical studies in the extant literature have investigated the income diversification, profitability, stability and efficiency nexus from various perspectives through various methodological approaches (Stiroh, 2004a, 2004b; Stiroh and Rumble, 2006; Chiorazzo et al , 2008; Lepetit et al , 2008; Elsas et al , 2010; Chronopoulos et al , 2011; Gamra and Plihon, 2011; Pennathur et al , 2012; Elyasiani and Wang, 2012; Gurbuz et al , 2013; Edirisuriya et al , 2015; Sarkar, 2016; Nisar et al , 2018; Doan et al , 2018; Vidyarthi, 2020; Luu et al , 2020). However, there is an acute paucity of literature regarding the determinants of bank income diversification.…”
Section: Introductionmentioning
confidence: 99%